Pengembangan Kuis dan Game Edukasi Menggunakan Wordwall pada Pembelajaran Daring Materi Persamaan Nilai Mutlak Bentuk Linear - Ilmi Inayati; I Nyoman Arcana; Agustinus Susetyo; Krida Singgih Kuncoro (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
This research aims to produce and determine the feasibility and attractiveness of educational quizzes and games using Wordwall, as well as the correlation between student responses and learning outcomes that are suitable for online learning on Linear Form Absolute Value Equations for grade 10. The research method used is the Research and Development (R&D) method with the ADDIE model, consisting of 5 stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation; (5) Evaluation. The expert validators consist of 2 mathematics education lecturers and 1 mathematics teacher. The research was conducted at MAN 2 Brebes with 40 grade 10 students. Data collection techniques used were product validation questionnaires, student response questionnaires, and quizzes in test form. The results of the material and media expert validation questionnaires on educational quizzes and games obtained an average feasibility percentage of 77.67% and 74.67%, categorized as "Feasible". The data analysis technique used is the feasibility percentage analysis and correlation analysis. The results showed that the product development of quizzes and educational games using Wordwall in online learning the absolute value equation for the linear form of class X was feasible to use. The implication is that the educational games and quizzes developed can be used as teaching materials; and teachers are advised to make educational games and quizzes for other subjects.